INFLUENCE OF SUPPLY CHAIN SUSTAINABILITY ON PERFORMANCE OF COMPANIES IN THE OIL INDUSTRY IN KENYA. - Ngugi, Christine Afandi; Kihara, DR. Allan (International Journal of Supply Chain and Logistics, 2019)
Purpose: The purpose of the study was to examine the influence of supply chain sustainability on performance of companies in the oil industry in Kenya with an aim of making recommendations on proper use of supply chain sustainability strategies. The study aimed at establishing how reverse logistics management, information technology adoption, early vendor involvement and green procurement adoption influences performance of companies in the oil industry. To achieve this, the study reviewed both theoretical and empirical literature and proposed the research methodology that addressed the gaps identified in literature as well as answer the stipulated research questions. Methodology: This research study adopted a descriptive research design approach targeting procurement staff at the 53 oil companies. This method is preferred because it allows an in-depth study of the subject. To gather data, structured questionnaire was used to collect data from 159 procurement officers, who were selected using simple random sampling, from the three strata. Once collected, data was analysed using descriptive and inferential statistics. Quantitative data was analysed using multiple regression analysis. The qualitative data generated was analysed by use of Statistical Package of Social Sciences (SPSS) version 22. Results: The response rate of the study was 75%. The findings of the study indicated that reverse logistics management, information technology adoption, early vendor involvement and green procurement adoption have a positive relationship with performance in companies in the oil industry. Contributions to policy and practice: The study recommended that companies in the oil industry should embrace supply chain sustainability so as to improve performance and further researches should to be carried out in other institutions to find out if the same results can be obtained.